8(t-3)+4t=6(2t+3)-13

Simple and best practice solution for 8(t-3)+4t=6(2t+3)-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(t-3)+4t=6(2t+3)-13 equation:


8 (t-3)+4t=6 (2t +3)-13

We simplify the equation to the form, which is simple to understand
8(t-3)+4t=6(2t+3)-13

Reorder the terms in parentheses
+(+8t-24)+4t=6*(2t+3)-13

Remove unnecessary parentheses
+8t-24+4t=+6+*(+2t+3+)-13

Reorder the terms in parentheses
+8t-24+4t=+(+12t+18)-13

Remove unnecessary parentheses
+8t-24+4t=+12t+18-13

We move all terms containing t to the left and all other terms to the right.
+8t+4t-12t=+18-13+24

We simplify left and right side of the equation.
t=+29

0=29

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| x^2+.56x^2=400 | | x^2+.56x^2=20 | | 15x^4+29x^3-14x^2=0 | | y=1ox-3 | | 2x-8=(x+2) | | 5-3(x-2)=8-(4-2x) | | 89+84=78 | | 9b^3+15b^2-36b= | | 35=0.42*w | | 3b^3+15b^2-36b= | | 84++89+=78 | | 3.375=p*37.5 | | a+18=7 | | .35*w=42 | | (3/2)c+c=20 | | 6v^2-19+10= | | Y=2x^3-9x^2+10x-3 | | 24a^3-16a^2= | | w^2-14w+40= | | 6x^2+48x-73=0 | | t^2+3t-40= | | 2.5(x+8)=12.8+1.6x | | v^2+5v+4= | | 9/4=36 | | 7(t-6)+5t=6(2t+2)-10 | | x+3/4=20 | | 3p-10=15 | | 6t-4t+5t-3t= | | 5y+3y-4y+7y= | | 3m-4m+5m-6m-m+5m= | | -(3y+2)-(-2y-4)=-4 | | -56x^7-7x^6= |

Equations solver categories